2017
DOI: 10.1111/dmcn.13524
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological mechanisms and functional impact of mirror movements in children with unilateral spastic cerebral palsy

Abstract: Mirror movements may be indicative of the underlying corticospinal tract reorganization in children with unilateral spastic cerebral palsy (CP). Future research will benefit from systematic investigations of the relationship between mirror movements and its pathophysiology. Mirror movements may be a potential biomarker for individualized medicine in children with unilateral spastic CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 30 publications
0
31
0
Order By: Relevance
“…Mirror movement scores of the affected hand (task performed by the unaffected hand) Poor motor outcome supported by our findings. 27 The persistence of ipsilateral corticospinal pathways connecting the unlesioned motor cortex to the affected hand is well established by previous TMS studies, 6,15,16,28 several of which concluded that stimulation of the unlesioned hemisphere may only elicit bilateral motor evoked potentials in those with 'intense' mirror movements. More recently, this same pattern was well characterized in children with perinatal stroke, 25,29 including evidence of common control mechanisms in the contralesional hemisphere of children with ipsilateral projections.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Mirror movement scores of the affected hand (task performed by the unaffected hand) Poor motor outcome supported by our findings. 27 The persistence of ipsilateral corticospinal pathways connecting the unlesioned motor cortex to the affected hand is well established by previous TMS studies, 6,15,16,28 several of which concluded that stimulation of the unlesioned hemisphere may only elicit bilateral motor evoked potentials in those with 'intense' mirror movements. More recently, this same pattern was well characterized in children with perinatal stroke, 25,29 including evidence of common control mechanisms in the contralesional hemisphere of children with ipsilateral projections.…”
Section: Discussionmentioning
confidence: 90%
“…Despite this data supporting the relationship between mirror movements and motor outcomes, it is important to consider that many other factors may contribute to function. As Kuo et al point out in a recent review, lesion type, size, location, possibly timing, and probably other factors may be implicated in motor function. It therefore becomes challenging to determine to what extent mirror movements alone impact this outcome and future studies may attempt to better tease apart these factors.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the presence of an ipsilateral projection (for both CSTbilat and CSTipsi) could explain the presence of MM, as proposed by various studies [11][12][13] , the high MM-similarity found in the CSTcontra group with a CSC lesion is obviously not due to the presence of an ipsilateral CST. In this case, a lack of interhemispheric inhibition could be the pathophysiological mechanism underlying MM in the less-affected hand 7 . Future studies should include neurophysiological techniques of interhemispheric inhibition to confirm this hypothesis in children with CSTcontra and CSC lesions.…”
Section: The Multifactorial Interaction Explaining the Variability Inmentioning
confidence: 76%
“…Second, cyclic passive movements in one joint could evoke repetitive motor responses in “remote” muscles of both ipsilateral (Figure 6) and contralateral (Figure 7) limbs, possibly also related to the so-called “irradiation” of responses to mechanical stimulation to distant muscles in infants (Myklebust and Gottlieb, 1993; Teulier et al, 2011). The contralateral effects can also be observed in adults in some conditions or pathologies (for instance, the phenomenon of “cross education” (Lee and Carroll, 2007) and “mirror movements” Carson, 2005; Kuo et al, 2018), although such effects generally take place during voluntary rather than passive movements.…”
Section: Discussionmentioning
confidence: 99%